2018
DOI: 10.1111/pde.13640
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat necrosis of the newborn and associated hypercalcemia: A systematic review of the literature

Abstract: Subcutaneous fat necrosis of the newborn is an uncommon disorder, and although usually benign, associated hypercalcemia can lead to complications such as failure to thrive and renal failure. Many sources suggest screening for hypercalcemia for 6 months following resolution of skin lesions, but little data are available to support this recommendation. This study examines existing published literature to better guide practitioners regarding screening evaluations of asymptomatic patients with subcutaneous fat nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 43 publications
(108 reference statements)
2
83
1
17
Order By: Relevance
“…Stefanko et al postulated that hypercalcaemia screening until 6 months of age was over-conservative, and recommended hypercalcaemia screening at diagnosis, and again at 30, 45 and 60 days post-resolution of skin lesions. They recommend rescreening if there are any concerns regarding hypercalcaemia within 6 months of resolution of skin lesions 1. Our data support the more conservative approach, as adopted by Del Pozzo-Magana, as detailed below 3…”
Section: Literature Searchsupporting
confidence: 82%
See 3 more Smart Citations
“…Stefanko et al postulated that hypercalcaemia screening until 6 months of age was over-conservative, and recommended hypercalcaemia screening at diagnosis, and again at 30, 45 and 60 days post-resolution of skin lesions. They recommend rescreening if there are any concerns regarding hypercalcaemia within 6 months of resolution of skin lesions 1. Our data support the more conservative approach, as adopted by Del Pozzo-Magana, as detailed below 3…”
Section: Literature Searchsupporting
confidence: 82%
“…Hypercalcaemia resolved within 28 days in 54% (15/28) of cases. This is lower than in other reviews which found that 76% of hypercalcaemia resolved within 28 days 1. Stefanko et al postulated that hypercalcaemia screening until 6 months of age was over-conservative, and recommended hypercalcaemia screening at diagnosis, and again at 30, 45 and 60 days post-resolution of skin lesions.…”
Section: Literature Searchmentioning
confidence: 82%
See 2 more Smart Citations
“…There is a lack of evidence coming from randomized controlled studies, as recently pointed out in a comprehensive review that included only case series and case reports. 8 Several studies have reported so far the use of bisphosphonate products to manage severe neonatal hypercalcemia. Use of pamidronate was reported by Samedi et al in two infants with severe hypercalcemia associated with SCFN following therapeutic hypothermia for hypoxic-ischemic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%